Dominant Consumption Rituals and Intragroup Boundary Work: How Non-Celebrants Manage Conflicting Relational and Identity Goals. Issue 3 (28th May 2015) - Weinberger, Michelle F.
Abstract : Through collective engagement in consumption rituals, group members reinforce intragroup relationships and the boundaries of the group. Yet, paradoxically, as intragroup diversity increases, dominant rituals deployed for this relational work, can run counter to the ideologically rooted identities of some members. Using a sociological lens, this article focuses on the complexities of not celebrating a dominant collective consumption ritual by focusing on people who do not celebrate Christmas in America. The qualitative data analysis finds that non-celebrants use a set of ritual strategies that are grounded in their conflicting goals of protecting their ideologically rooted identities but also doing relational work with celebrators. It shows how non-celebrants deploy consumptive elements of the dominant ritual as symbolic resources to enact each strategy, foregrounding or backgrounding the symbolic boundary between themselves and celebrators. Beyond the context, contributions to the study of symbolic boundaries, identity politics, and collective consumption rituals are discussed.